Análise experimental de blocos de concreto com função estrutural produzidos com agregados leves - Micheviz, Juliana (2011)
Construction techniques are developed and improved with the help of tests and observation. Constructions based upon a self-supporting concept have been made for thousands years and with technological evolution they now stand for a quick and practical solution for usage in building sites. Following this concept, this paper researched the feasibility of replacing conventional aggregates in the manufacture of concrete blocks by lightweight materials, so that the blocks keep the same structural function according to ABNT NBR 6136/2007. The aggregates commonly used in the production of concrete blocks are crushed stone 0 and medium sand. The purpose of this paper is the use of exfoliated vermiculite as a substitute for sand; and exclay, for crushed stone 0, because they are lightweight composites with equivalent dimensions. The use of lightweight aggregates in structural concrete block production can produce benefits such as reduction in depth of the foundations of the design (bringing down the weight of the structure itself), as well as buildings that can not suffer increased load on their structures and may undergo renovations. Therefore the employment of lighter materials seems a good alternative to the conventional one. Furthermore the chosen lightweight aggregates have also been proven with good thermal and acoustic performances, however these features were not studied in this paper. Blocks were performed with conventional aggregates to determine the reference mark, which was utilized for the production of blocks with replacements of 0%, 50% and 100% of conventional aggregates by exclay and exfoliated vermiculite. The used method was the fractional factorial response surface, which suited to determine the optimal mark with the replacement of aggregates in concrete. This statistical method was the most feasible, since it has reduced the number of producing and testing samples, moreover it was possible to reach a result of a greater proportion of lightweight aggregates with less materials and time savings.